2019
DOI: 10.4103/ijmpo.ijmpo_70_18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcomes of Non-Hodgkin's lymphoma in children: A report from a tertiary care hospital from India

Abstract: Background: Non-Hodgkin's lymphoma (NHL) is an aggressive malignancy. Its outcome has improved over the past decades. Although it accounts for 8%–10% of all childhood cancers, very less information about its clinical presentation and outcomes is available from India. Our objective was to study the clinical presentation and outcomes in children (<15 years) with NHL at our center. Methodology: We retrospectively analyzed 26 children diagnosed with NHL at our center from August 2008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…5 Most patients of HL usually present with B symptoms (fever, drenching night sweats and loss of more than 10% of weight in the last 6 months), while NHL patients present commonly with abdominal swelling followed by lymphadenopathy. 14,15 In this study, lymphadenopathy was the most common presentation in both HL and NHL patients. These patients are often misdiagnosed as tuberculosis that leads to advanced stage at diagnosis.…”
Section: Discussionmentioning
confidence: 67%
“…5 Most patients of HL usually present with B symptoms (fever, drenching night sweats and loss of more than 10% of weight in the last 6 months), while NHL patients present commonly with abdominal swelling followed by lymphadenopathy. 14,15 In this study, lymphadenopathy was the most common presentation in both HL and NHL patients. These patients are often misdiagnosed as tuberculosis that leads to advanced stage at diagnosis.…”
Section: Discussionmentioning
confidence: 67%
“…15 studies [ 9 , 21 , 24 27 , 32 , 34 , 39 41 , 44 , 49 – 52 ] ( n = 4258, range per study n = 18 to 2326) reported on the symptoms and signs for non-Hodgkin’s lymphoma. These included organomegaly (34% [95% CI 22%-48%]), B-symptoms (38% [95% CI 31%-44%]), cervical lymphadenopathy (28% [95% CI 17%-42%]), peripheral lymphadenopathy (45% [95% CI 31%-61%]), fever (47% [95% CI 35%-61%]), weight loss (58% [95% CI 41%-72%]), abdominal pain (29% [95% CI 12%-54%]) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During the assessment and diagnostic approaches of suspected children with NHL, some pathological conditions like vena cava obstruction, acute airway obstruction, intestinal obstruction, spinal cord compression, pericardial tamponade, lymphomatous meningitis, hyperuricemia, tumor lysis syndrome, ureteral obstruction, unilateral or bilateral hydronephrosis, venous thromboembolic disease, and a potential emergency complication of NHL may be present [ 12 ]. Because some of those are fetal and may cause death during the initial stage of treatment, those initial parameters are important and documented.…”
Section: Introductionmentioning
confidence: 99%